Anxious Joburg : the inner lives of a global south city - Falkof, Nicky; Van Staden, Cobus (Wits University Press, 2020)
Anxious Joburg is a rigorous, critical new discussion of Johannesburg as a paradigmatic example of a contemporary global South city. It considers localised manifestations of the late capitalist experience of pervasive anxiety as a structuring principle of urban life, and provides snapshots of the daily lived experience in this city.